Wybrane nadużycia w sporcie w świetle prawa karnego = Main sports malpractices in the view of criminal law - Klimczyk, Agata (Journal of Education, Health and Sport, 2015)
Klimczyk Agata. Wybrane nadużycia w sporcie w świetle prawa karnego = Main sports malpractices in the view of criminal law. Journal of Education, Health and Sport. 2015;5(8):295-301. ISSN 2391-8306. DOI 10.5281/zenodo.28774 http://dx.doi.org/10.5281/zenodo.28774 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A295-301 https://pbn.nauka.gov.pl/works/611153 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-278a75e8-caa1-4539-95bc-23ce54e2a1bd Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2015. Revised 21.08.2015. Accepted: 21.08.2015. Wybrane nadużycia w sporcie w świetle prawa karnego Main sports malpractices in the view of criminal law Agata Klimczyk Nicolaus Copernicus University in Toruń Streszczenie Celem publikacji jest przedstawienie problemu korupcji w sporcie, ze szczególnym uwzględnieniem odpowiedzialności karnej. W pracy dokonano analizy raportów Centrum Badania Opinii Społecznej, a także posiłkowano się przeglądem specjalistycznej literatury. Wykazano jak dużym problemem jest korupcja w sporcie, a także w jaki sposób należy jej przeciwdziałać. Stwierdzono, że bez odniesienia się do zasad fair play sport w pełnym tego słowa znaczeniu, nie ma racji bytu. Słowa kluczowe: sport, nadużycia, prawo karne. Abstract The main aim of this work is to show sports corruption with special regard to criminal responsibility. In this work was used following methods: analysing reports of polish Centre for Public Opinion Research and it was made review of special literature. The author shows, how great problem is sports corruption and how to deal with it. It was alleged that sport is completly at odds without fair play rules. Key words: sport, malpractices, criminal law.